Reimagining philanthropy in the Global South : from analysis to action in a post-COVID world - Woodcraft, Clare, 1968-; Munir, K. (Kamal); Khemka, Nitya Mohan; El-Erian, Mohamed A., 1958- (Cambridge University Press, 2024)
While there have always been high levels of philanthropic giving in the Global South, the urgency and unexpectedness of COVID-19 transformed the parameters within which philanthropy operates. 'Reimagining Philanthropy in the Global South' examines how newer models of philanthropy are tackling development challenges, including poverty, inequality and access to healthcare and education, and questions how organisations are coping with structural changes in donor-driven philanthropy; how changes in traditional grant making are impacting the imperatives of recipient organisations; and how indigenous philanthropy is making a difference. The chapters provide frank assessments of the priorities, challenges and opportunities of emerging market philanthropy, and the lessons learned from the pandemic. The authors highlight the deeper issues at play, as well as offering ideas and positive examples of how diverse stakeholders are coming together to solve social challenges in creative and practical ways. This title is also available as Open Access on Cambridge Core.